Aging, cancer, and autophagy: connections and therapeutic perspectives - Begoña Zapatería; Esperanza Arias; Esperanza Arias (Frontiers in Molecular Biosciences)
Aging and cancer are intricately linked through shared molecular processes that influence both the onset of malignancy and the progression of age-related decline. As organisms age, cellular stress, genomic instability, and an accumulation of senescent cells create a pro-inflammatory environment conducive to cancer development. Autophagy, a cellular process responsible for degrading and recycling damaged components, plays a pivotal role in this relationship. While autophagy acts as a tumor-suppressive mechanism by preventing the accumulation of damaged organelles and proteins, cancer cells often exploit it to survive under conditions of metabolic stress and treatment resistance. The interplay between aging, cancer, and autophagy reveals key insights into tumorigenesis, cellular senescence, and proteostasis dysfunction. This review explores the molecular connections between these processes, emphasizing the potential for autophagy-targeted therapies as strategies that could be further explored in both aging and cancer treatment. Understanding the dual roles of autophagy in suppressing and promoting cancer offers promising avenues for therapeutic interventions aimed at improving outcomes for elderly cancer patients while addressing age-related deterioration.